Région n° 4... et France entière : Allier, Aube, Belfort (Territoire de), Cher, Côte d'Or, Creuse, Doubs, Indre, Indre-et-Loire, Jura, Loir-et-Cher, Loire, Loiret, Maine-et-Loire, Haute-Marne, Nièvre, Puy-de-Dôme, Rhône, Haute-Saône, Saône-et-Loire, Deux-Sèvres, Vendée, Vienne, Haute-Vienne, Vosges, Yonne - Lesage, Adolphe-Auguste (1862-1952)
fig., cartes, graph., tabl.